2018
DOI: 10.3892/ol.2018.8801
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑29c restores cisplatin sensitivity in liver cancer through direct inhibition of sirtuin 1 expression

Abstract: Liver cancer is one of the most prevalent human tumors in the world. Despite recent advances regarding the understanding of the molecular basis of liver cancer and the introduction of novel chemotherapeutic approaches, liver cancer remains associated with a poor prognosis. Sirtuin 1 (SIRT1) was identified to be abnormally upregulated in liver cancer. Dysregulation of microRNAs (miRs/miRNAs) is associated with a variety of types of cancer, and miRNAs may also serve a role in tumorigenesis and progression. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…miR-29c was previously reported to play a tumor-suppressive role by targeting key pathways in cancer and CSC population [ 49 , 50 ]. Furthermore, ectopic miR-29c expression sensitizes cancer cells to paclitaxel chemotherapy [ 51 ]. Similarly, ID2 expression in cancer is also correlated with self-renewal ability and resistance to chemotherapy [ 52 , 53 ], suggesting the significance of miR-29c and ID2 axis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…miR-29c was previously reported to play a tumor-suppressive role by targeting key pathways in cancer and CSC population [ 49 , 50 ]. Furthermore, ectopic miR-29c expression sensitizes cancer cells to paclitaxel chemotherapy [ 51 ]. Similarly, ID2 expression in cancer is also correlated with self-renewal ability and resistance to chemotherapy [ 52 , 53 ], suggesting the significance of miR-29c and ID2 axis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, miR-362 and miR-505 overexpression were observed in gastric cancer cells ( Xia et al, 2014 ; Wang Z. et al, 2020 ), and their enhanced expression promoted nuclear accumulation of NF-κB/p65, due to both miRs targeted CYLD directly and its downregulation mediated NF-κB activation. Besides, Zhang and Luo found that miR-29c was downregulated in HepG2/DDP cells, and demonstrated that miR-29c targeted SIRT1 ( Zhang and Luo, 2018 ). SIRT1 may have enhanced activity in tumor cell growth by promoting NF-κB expression ( Yeung et al, 2004 ).…”
Section: Micrornas Involved In Ddp-chemoresistancementioning
confidence: 99%